Cement-content determination for grouts and grouted soils. Issue 3 (20th August 2021) - Kainrath, Adrian; Adam, Dietmar; Hornich, Wolfgang
Abstract : Permeation grouting is a common technique for ground improvement and cement-based grouts are the most widely used grouting materials to fill the voids of granular soil, with the purpose of reducing its permeability and improving its strength. Using the cement content, essential strength and permeability, predictions can be made. Unfortunately, once the grout has penetrated the soil, the final cement content in the soil cannot be estimated due to a lack of qualified methods. This paper presents a new approach to determine the cement content of hardened grouts and grouted soil, based on the estimation of the chemically bound water, which is an integral part of hydrated cement. Due to the high water-to-cement ratio of cement-based grouts, the hydration process occurs very quickly. Therefore, a fundamental correlation can be derived between the chemically bound water and the cement content. The chemically bound water in grouted soil samples can be determined through the water loss at different heating temperatures. This paper presents the developed theoretical principles based on systematic tests on hydrated grouts. Furthermore, evaluation tests to determine the cement content of grouted soil specimens were carried out and are discussed in this paper.